2023
DOI: 10.1111/andr.13534
|View full text |Cite
|
Sign up to set email alerts
|

Genetically proxied intestinal microbiota and risk of erectile dysfunction

Fuxun Zhang,
Yang Xiong,
Yangchang Zhang
et al.

Abstract: BackgroundThe interaction between intestinal microbiota and erectile dysfunction (ED) is less investigated. This study was performed to explore the association between intestinal microbiota and ED.MethodsIn this two‐sample Mendelian randomization (MR) study, genetic variants of gut microbiota were obtained from MiBioGen consortium containing 18,340 individuals. Six methods including inverse variance weighting (IVW), MR‐Egger, weighted median, maximum likelihood, MR robust adjusted profile score, and MR pleiotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The main etiology of PPI was vasculogenic tower (51.8%), diabetes (18.8%) and pelvic trauma /spinal cord injury (12.5%) in China. 11,12 Despite the data above shows that high cost and relatively low patient acceptance have limited the use of PPI in China, among patients with refractory ED in China, those in need of young and middle-aged patients are more likely to accept, in order to maintain marriage, family stability, and sexual partner relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The main etiology of PPI was vasculogenic tower (51.8%), diabetes (18.8%) and pelvic trauma /spinal cord injury (12.5%) in China. 11,12 Despite the data above shows that high cost and relatively low patient acceptance have limited the use of PPI in China, among patients with refractory ED in China, those in need of young and middle-aged patients are more likely to accept, in order to maintain marriage, family stability, and sexual partner relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Oscillibacter is able to maintain gut pH balance by producing substances such as propionate and butyrate, thus promoting the health and stability of the intestinal mucosa [63,64]. Therefore, these two types of bacteria are generally considered beneficial, but their imbalance or depletion has been closely associated with inflammatory bowel disease, obesity, and other related conditions [65]. The results of the present study showed that the relative abundance of Lactobacillus and Shigella was significantly increased in DSS-induced UC, which is also consistent with the findings of Schirmer M [66].…”
Section: Discussionmentioning
confidence: 99%